WILL AN INCREASE IN LANDHOLDING SIZE REDUCE CHILD LABOUR IN THE PRESENCE OF UNEMPLOYMENT? A THEORETICAL ANALYSIS - Chakraborty, Kamalika; Chakraborty, Bidisha (Economic Annals, 2019)
This paper builds an over-lapping generations household economy model in a rural set up and examines the relationship between landholding and child labour in the presence of unemployment in the manufacturing sector. We find that ir-respective of whether the parents work as agricultural labourers or work on their own land, an increase in landholding size leads to a decline in the child worker’s schooling in the short run and a decline in the growth rate of human capital formation in the long run, but may lead to an increase in steady state human capital in the long run.